Peranan dan Pola kegiatan Wanita di Sektor Informal (Khususnya Pedagang Sayur di Pasar) - Romany Sihite (Antropologi Indonesia, 1992)
In this article some characteristics of women petty vegetable traders from five markets in Pulo Gadung, Jakarta are put forward. Writer had conducted a study of these women at the beginning of 1991. Most of these traders have migrated to Jakarta to look for better living conditions. They work because they have to support their families. They have very long working hours, receive low financial reward, but even though the earnings are very small, the survival of their families depend heavily on these earnings.